Representações sociais de alunos e professores do curso de Moda respeito do mercado consumidor (ModaPalavra e-periódico, 2012)
The thesis goal is to investigate social representation of fashion graduated students and its teachers regarding consumer market. The research was based on the “Social Representation theory” and also in consumer market studies. The study was conducted on the two major teaching Institutions that offer for a long time a graduation course in Rio de Janeiro.
Keywords: Consumer Market; Social Representations; Fashion; Students; Teachers